2017
DOI: 10.28978/nesciences.348449
|View full text |Cite
|
Sign up to set email alerts
|

Climatic Trends in the Temperature of Çanakkale City, Turkey

Abstract: Climate is a dynamic process changing in both temporal and spatial scales. Climate change and global warming has been extensively accepted and commonly described as rising of the temperature. Long-term trends and changes in the series of monthly, seasonal and annual temperature of Çanakkale station (Çanakkale, Turkey) of Turkish State Meteorological Service (TSMS) were analyzed by considering temporal characteristics. Climatic data for temperature encompasses the period of between 1970 and 2012. Temperature da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 46 publications
2
12
0
3
Order By: Relevance
“…Benzer şekilde, birçok çalışmada iklim değişikliğinin su kaynaklarını etkilediği rapor edilmiştir (Kale vd., 2016a;Kale vd., 2016b;Ejder vd., 2016a;Ejder vd.,2016b;Kale vd., 2018;Kale ve Sönmez, 2018a;Kale ve Sönmez, 2018b;Kale ve Sönmez, 2019a;Kale ve Sönmez, 2019b;Kale ve Sönmez, 2019c;Kale ve Acarlı, 2019a;Kale ve Acarlı, 2019b;Sönmez ve Kale, 2020). Ayrıca, Çanakkale ili için de iklim değişikliği nedeniyle sıcaklık (Kale, 2017a) ve buharlaşma (Kale, 2017b) eğilimlerinin değiştiği ve gelecekte daha çok artacağı tahmin edilmektedir. Dolayısıyla, bu bölgedeki denizel biyolojik çeşitliliğin iklim değişikliğinin olumsuz etkilerinden korunması biyoçeşitliliğin sürdürülebilirliğinin sağlanması açısından hayati önem taşımaktadır.…”
Section: Mevsimunclassified
“…Benzer şekilde, birçok çalışmada iklim değişikliğinin su kaynaklarını etkilediği rapor edilmiştir (Kale vd., 2016a;Kale vd., 2016b;Ejder vd., 2016a;Ejder vd.,2016b;Kale vd., 2018;Kale ve Sönmez, 2018a;Kale ve Sönmez, 2018b;Kale ve Sönmez, 2019a;Kale ve Sönmez, 2019b;Kale ve Sönmez, 2019c;Kale ve Acarlı, 2019a;Kale ve Acarlı, 2019b;Sönmez ve Kale, 2020). Ayrıca, Çanakkale ili için de iklim değişikliği nedeniyle sıcaklık (Kale, 2017a) ve buharlaşma (Kale, 2017b) eğilimlerinin değiştiği ve gelecekte daha çok artacağı tahmin edilmektedir. Dolayısıyla, bu bölgedeki denizel biyolojik çeşitliliğin iklim değişikliğinin olumsuz etkilerinden korunması biyoçeşitliliğin sürdürülebilirliğinin sağlanması açısından hayati önem taşımaktadır.…”
Section: Mevsimunclassified
“…These changes could be related to the climatic changes such as rising temperature, declining precipitation, increasing evaporation, decreasing surface runoff and snow melting. Similarly, Kale (2017a) reported that the temperature had an increasing trend in addition to the document reported by Kale (2017b) claiming that evaporation had increasing trend in Çanakkale for future periods. Moreover, Ejder et al (2016a) noted that annual streamflow of Sarıçay Stream was decreasing and streamflow presented a decreasing trend.…”
Section: Figure 2 Temporal Change In Water Surface Areamentioning
confidence: 85%
“…The city was divided by the Çanakkale Strait and located on both Asia and Europe continents. The climate in Çanakkale is typical transition climate which winter is rainy and cold, and summer is dry and hot (Kale 2017a). Atikhisar Reservoir (Figure 1) was built on Sarıçay Stream which it has its source from Ida Mountains and runs into Çanakkale Strait (Ejder et al, 2016a).…”
Section: Study Areamentioning
confidence: 99%
“…There are many studies about trend analysis on climatic parameters such as temperature (Türkeş et al, 1996;Han et al, 2012;Limjirakan and Limsakul, 2012;Demir et al, 2008;Duman and Kara, 2017;Kale, 2017a), evaporation (Tebakari et al, 2005;Jaswal et al, 2008;Kale, 2017b;Bacanlı and Tanrıkulu, 2017), and precipitation (Partal and Kahya, 2006;Aslantaş Bostan andAkyürek, 2007, 2010;Kızılelma et al, 2015;Doğan Demir and Demir, 2017;Yavuz and Erdoğan 2012;Bacanlı and Tanrıkulu, 2016;Bacanli, 2017;Taylan and Aydın, 2018). Trend analyses were also carried out to determine the trends in the streamflow.…”
Section: Discussionmentioning
confidence: 99%